Senescence marker killer cell lectin-like receptor G1 (KLRG1) contributes to TNF-α production by interaction with its soluble E-cadherin ligand in chronically inflamed joints. Issue 6 (5th June 2013) - Melis, Lode; Van Praet, Liesbet; Pircher, Hanspeter; Venken, Koen; Elewaut, Dirk
Abstract : Objectives: Killer cell lectin-like receptor G1 (KLRG1) is an NK cell marker also expressed on T cells showing an immunosenescent phenotype. KLRG1 binding to its ligand E-cadherin inhibits functional responses. It was recently shown that soluble E-cadherin (sE-cadherin) also influences KLRG1 signalling, although its involvement in arthritis is unknown. Our goal was to evaluate the contribution of KLRG1 + T cells to synovitis. Methods: Paired peripheral blood (PB) and synovial fluid (SF) mononuclear cells from 21 patients with spondyloarthritis (SpA) or rheumatoid arthritis (RA), eight with crystal-induced arthritis and 10 controls were obtained. T cells were characterised for KLRG1 expression directly ex vivo, while TNF-α/IFN-γ production was assessed after polyclonal stimulation. Assays of chemotaxis response towards SF were conducted. Additionally, sE-cadherin levels in our paired samples were determined. Moreover, TNF-α/IFN-γ production by antigen-specific T cells was evaluated in the presence of sE-cadherin. Results: KLRG1 + T cells were enriched in SF as opposed to PB of SpA and RA patients, which contrasts with results obtained in crystal-induced arthritides. KLRG1 + T cells were more functionally active as opposed to KLRG1 − T cells and migrated preferentially towards SpA and RA SF. sE-cadherin levels were higher in SF versus plasma. The presence of sE-cadherin enhanced the number of KLRG1 + CD4 + T cells able to produce TNF-α but not IFN-γ. Conclusions: sE-cadherin contributes to the local proinflammatory environment in the joint by favouring TNF-α production by KLRG1 + CD4 + T cells. This pathway seems to be operational in both SpA and RA, but not in crystal-induced arthritis.